Differences between colonies and chick-rearing stages in Imperial Cormorant (Phalacrocorax atriceps) diet composition: Implications for trophic studies and monitoring - Ibarra, Cynthia (2018)
We assessed differences in diet composition between Imperial Cormorants (Phalacrocorax atriceps) breeding at Isla Arce and Isla Vernaci Este, Golfo San Jorge, Argentina. Both colonies are located within the Patagonia Austral marine park, and commercial trawl fisheries operate in adjacent waters, thus knowledge of their food requirement is fundamental to assess potential conflicts and monitor interactions. We obtained stomach samples from 63 adult Imperial Cormorants during the chick-rearing period in 2014: 32 at Isla Arce and 31 at Isla Vernaci Este. We recorded 27 and 30 prey taxa in stomach samples at Isla Arce and Isla Vernaci Este, respectively, and at least 21 were common to both islands. Significant differences in diet composition in terms of importance by mass were found between young and old chick stages at Isla Arce but not at Isla Vernaci Este. Rock cod (Patagonotothen spp.) were dominant at Isla Vernaci Este during both chick stages (75.7% and 86.5%, respectively). At Isla Arce, rock cod, Argentine anchovy (Engraulis anchoita), and Argentine hake (Merluccius hubbsi) contributed similarly to their diet (26-33%) during the young chick stage, whereas Argentine anchovy dominated during the old chick stage (76.6%). Diet composition in terms of importance by mass was significantly different between colonies. Imperial Cormorant consumed benthic, demersal, and pelagic prey, confirming plasticity in feeding habits, but their contribution differed depending on the site and chick stage. Our results suggest that diet assessments and monitoring the potential interaction between Imperial Cormorant and fisheries should not be based on information from a single breeding stage or location, but requires the analysis of diet composition throughout the breeding cycle with a representative sampling of the 17 colonies within the marine park.